(untitled) (University of Khartoum Engineering Journal, 2022)
This study aims to evaluate the effect of using polypropylene plastic pellets as partial replacement of fine aggregate with percentages of 5% and 10% by volume on the properties of fresh and hardened concrete. For this purpose, three mixes were prepared, 18 cubes were cast for compressive strength, fresh density and dry density, also 9 cylinders were cast for splitting tensile strength and 9 beams were cast to determine the flexural strength. The resulting slump of the mixes increases as the plastic percentage increases. The fresh density, dry density compressive strength and splitting tensile strength values decrease compared to the control. The flexural strength increases with the percentage increase.